PEMIKIRAN KALAM ULAMA ANDALUSIA ABAD 8 H IBNU JUZAY AL-KALBI DALAM KITAB TAFSIRNYA: AL-TAS-HIL LI ‘ULUM AL-TANZIL (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2019)
This paper seeks to reveal a brief overview of the thought of Ibn Juzay through his interpretation of the Qur’an. The goal is to determine the pattern and characterisiques of the schools as part of the study of Islamic civilization in the western part of Islam (Andalusia and North Africa). In his case al-Tas-hil Li ‘Ulum al-Tanzil, he was able to interpret the Qur’an in just four volumes with all its characteristics and advantages. Through a literature review and with a content analysisapproach, the study found the fact that the doctrine of al-Ash’ariyah was in the style and interpretation of Ibn Juzayy al-Kalbi. However, he was able to rule out his ego by advancing the data evidence displayed in the book of his Tafseer.